Criminal Liability of Indonesia’s State-Owned Enterprise Directors for Acts That Cause State Financial Losses - Marune, Abraham Ethan Martupa Sahat (Interdisciplinary Social Studies, 2021)
Directors of state-owned enterprises can be prosecuted because of suspicions of their actions which cause state finances loss. The objectives of this research is to find out the responsibilities of directors which cause state finances loss. This research used normative juridical methods.b The research found that the directors of state-owned enterprises were assumed as state officers. State-owned company assets were interpreted as state assets, as well as state loss was interpreted as state finance loss. In administrative law, when directors of state-owned enterprises do an action that causes state financial loss, they are obliged to return the loss, but in criminal law, returning the loss will not eliminate the penalty of the criminal.